Arts And Folklor Resources As Attraction And Development Of Indonesian Cultural Tourism - Priyanto, Priyanto; Dewi, Nur Fadilah (UI Scholars Hub, 2020)
Art and folklore is a culture that has been passed down from the ancestors. Folklore is often used as research material and study material. Folklore must be used properly so that it can be useful for everyone. Folklore art itself has many elements such as artistic elements, namely drama, sound, literature, music, movement and fine arts. Folklore art is also one of the development tools in the tourism sector for schools, campuses, cultural villages, tourist attractions and other historical buildings. The use of folklore art can increase knowledge for children today, where culture in Indonesia must be sought first and it can be said that the culture in Indonesia has begun to decrease due to cultural acculturation. Through folklore, they can quickly gain knowledge about previous cultures that already exist and have been passed down from their ancestors. This research uses a qualitative method. The results showed that art and folklore have many benefits for the tourism sector. This paper will explain about how to use art and folklore for the development of Indonesia's tourism sector.